PENINGKATAN KESADARAN MASYARAKAT TERHADAP KEBERSIHAN DAN MENGEMBANGKAN UMKM DI KELURAHAN BAKALANKRAJAN - Firnanda Al Islama Achyunda Putra; Rizza Muhammad Arief; Yulia Natasya Farah Diba Arifin (RAMBIDEUN : Jurnal Pengabdian Kepada Masyarakat, 2024)
Improving cleanliness is one way to optimize public health. This community service activity has the theme of cleanliness and development of MSMEs, which is carried out by KKN students in Bakalankrajan Village. Students helped develop 2 MSME products and held a "Shining Village" competition to increase the enthusiasm and awareness of residents in cleaning the environment. This activity aimed to increase residents' awareness and initiative towards environmental cleanliness in Bakalankrajan Village. From the results of the "Shining Village" competition, Unmer KKN 2023 students will support and help the village that gets the lowest score. This activity used implementation methods in the form of socialization, by distributing posters, holding competitions, assessing and processing scale data, and service in the form of community service. From the results of the service activities, it can be seen that residents are starting to keep their environment clean after the Shining Village" competition program and updating the logo and catalog design for the Jamu and Sago Tempe Chips MSMEs to maximize their products visibility.